Working (with/out) the system : educational leadership, micropolitics, and social justice - Ryan, James, 1952 October 18-; Armstrong, Denise E. (Issues in the research, theory, policy, and practice of urban education ;, 2016)
This edited collection of chapters from invited scholars, explores issues of social justice and micropolitics in educational institutions. More specifically, it examines the ways in which social justice workers navigate, or can navigate, (micro) political systems in their quest to promote social justice. Issues of social justice and micropolitics are particularly important in this day and age as standardizing regimes and polarizing forces continue to erode the already perilous condition of the traditionally disadvantaged. While social justice workers make it a point to acknowledge the plight of the less fortunate, their well-meaning attempts to take action are not always successful. This requires that they acknowledge the realities of the micropolitical environments in which they work, and to take action in these arenas if they are to achieve their social justice goals. The title of the book, Working (With/out) the System, draws attention to the ways in which social justice workers/leaders (teachers, administrators, students, community members) navigate educational institutions and the wider social systems that are not always hospitable to changes that promote social justice. This volume describes the prospects, possibilities and actual practice of working with, working without, and working outside of educational organizations to promote social justice. Among other topics, the chapters probe: - the manner in which social justice-minded leaders navigate micropolitical environments - the ways in which social justice minded leaders promote and sustain social justice action within systemic contexts - the difficulties and successes that they experience.